Spatial Analysis of Land Carrying Capacity in Wanggarasi District, Pohuwato Regency - Fitria S. Bagu; Zulzain Ilahude; Laode Muhamad Irsan (International journal of technology and education research, 2026)
Land use change and population growth are the main factors influencing the sustainability of land resource management, particularly in areas experiencing rapid development dynamics. This study aims to analyze the condition and changes in land carrying capacity in Wanggarasi Sub-district using a spatial and temporal analysis approach based on Geographic Information Systems (GIS). The research employs a descriptive quantitative method utilizing secondary data, including population data, land use data, and multi-temporal satellite imagery. The land carrying capacity index was calculated based on several indicators, namely the proportion of the farming population, the area of cultivated agricultural land, farmer involvement in non-agricultural activities, and the availability of land suitable for living. The results indicate that Wanggarasi Sub-district falls into the category of moderate land carrying capacity, with indications of imbalance between the high proportion of the farming population and the limited availability of productive agricultural land and land suitable for living. This condition reflects the presence of socio-ecological pressures that may increase the risk of land carrying capacity deficits if not accompanied by adaptive land management policies. Spatial analysis demonstrates that GIS is effective in identifying the spatial distribution and zoning of land carrying capacity in greater detail. This study is expected to serve as a basis for spatial planning and evidence-based policymaking to support sustainable regional development at the sub-district level.